AT MASS WITH SIR JAMES: MACMILLAN'S SYMPHONY NO. 4 AND LITURGICAL TIME. (6th September 2018) - Ward, Matthew
Abstract: Sir James MacMillan's Symphony No. 4 is claimed by the composer as an abstract work, but a clear programme is discernible through the use of references to the Roman Catholic Mass. MacMillan uses Gregorian chant, quotations from Robert Carver's Missa Dum sacrum mysterium (c. 1523) and his own St Luke Passion (2015) to create a liturgical form for the symphony. These allusions and their presentation in the symphony can be fruitfully understood in relation to Catholic theologies of time and the Eucharist. When allusions to sonata form are also taken into consideration, the result is a complex interaction between different experiences of time in the symphony's span.